Use of Andexanet Alfa for Factor Xa Inhibitor Reversal in US Verified Trauma Centers: A National Survey - Charles Fasanya MD, FRCS FACS; Abenámar Arrillaga MD FACS FCCP; Catherine Caronia MD, MBA; Lauren Rothburd BS; Tenzing Japhe BA; Younghee Hahn BS; Paul Joseph BS; Dajana Reci BA; Patricia Eckardt PhD, RN, FAAN (Clinical and Applied Thrombosis/Hemostasis, 2024)
Direct oral factor Xa inhibitors are replacing vitamin K-dependent antagonists as anticoagulation treatment in many clinical scenarios. Trauma centers are noting an increase in patients presenting on these medications. The 2018 Food and Drug Administration approval of andexanet alfa provides an alternative anticoagulation reversal. Barriers may limit utilization of new medications including a lack of grade 1A evidence supporting the use of prothrombin complex concentrate (PCC) versus andexanet alfa and cost. To evaluate barriers of andexanet alfa utilization by trauma surgeons, a 15-question survey was conducted. There was a 9% completion rate (n = 89). The results revealed 23.5% would choose andexanet alfa as first-line treatment in children, and 25.8% as first-line treatment in adults. The majority of respondents, 64.7% and 67.4%, would use PCC preferentially in children and adults, respectively. Respondents indicated that cost burden was an overriding factor (76.3%); 42.4% cited lack of high-level efficacy data of andexanet alfa for reversal of factor Xa inhibitors. Additional double-blinded multi-institutional randomized controlled trials comparing 4F-PCC and andexanet alfa for factor Xa inhibitor reversal are needed to support efficacy especially with the increased cost associated.